(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
Fairy tales are one of the richest sources of cultural heritage, reflecting the worldview, values, and imagination of different nations. This article presents a comparative analysis of magical language units in English and Uzbek fairy tales. Special attention is given to the linguistic forms, semantic features, and cultural meanings of magical expressions such as spells, formulas, symbolic words, and repeated structures. The analysis shows that while both traditions use magical language to create an atmosphere of wonder and transmit moral values, they differ in form, symbolism, and cultural background.